Data Communications And Computer Networks - Brijendra Singh (Prentice-Hall Of India Pv, 2011)
This fully revised book, now in its Third Edition, continues to provide a comprehensive coverage of data communications and computer networks in an easy to understand style. The text places as much emphasis on the application of the concepts as on the concepts themselves. While the theoretical part is intended to offer a solid foundation of the basics so as to equip the student for further study, the stress on the applications is meant to acquaint the student with the realistic status of data communications and computer networks as of now. In this edition, new topics such as Distributed Systems, Client Server Models, Wireless LAN, Network Security Tools, Web-based Application Servers, E-commerce, PGP (Pretty Good Privacy) and IP Security are included at appropriate places and some existing sections are also updated to enrich the contents. Intended primarily as a textbook for the students of computer science and engineering, electronics and communication engineering, master of computer applications (MCA), and those offering IT courses, this book would also be useful for practising professionals.